Restricted Dispersal in the Late Successional Forest Tree Species Nothofagus Pumilio: Consequences Under Global Change - Soliani, Carolina; Sekely, Jill; Zamora-Ballesteros, Cristina; Heer, Katrin; Lepais, Olivier; Mondino, Victor Alejandro; Opgenoorth, Lars; Pastorino, Mario Juan; Marchelli, Paula (Wiley, 2025)
Plants rely on gamete dispersal to ensure the inheritance of their genes. Gene flow, mediated by pollen and seed dispersal, also fosters species' cohesion across space, facilitates population migration, and influences local adaptation. Nothofagus pumilio is an ecologically important wind-dispersed tree species of the Patagonian Andes. We aim to uncover its current and historic effective dispersal distances and characterize its fine-scale genetic structure. In a naturally monospecific stand of N. pumilio, we sampled 200 adults and 400 seedlings. Using a modern sequencing approach (SSRseq), we developed 15 nuclear microsatellite markers for genotyping and used them to characterize genetic diversity and fine-scale genetic structure. We estimated dispersal distances using direct methods (i.e., neighborhood models) and indirect (i.e., inferred from fine-scale spatial genetic structure). Short average seed and pollen dispersal distances were estimated (δs = 13.33 m and δp = 24.08 m respectively), but the fat-tailed distribution of dispersal kernels also suggests some immigration and long-distance dispersal events. Indirect estimates (σ2g = 21.62) are closely aligned with direct estimates. The majority of seedlings (84%) could be assigned to at least one sampled adult within the plot, and these seedlings were produced by just 43% of sampled adults. Reproductive success was significantly associated with seed donors' diameters at breast height. N. pumilio's distribution expansion capacity may be limited by short seed dispersal distances, especially in the context of global change. Natural and assisted migration actions should be prioritized to mitigate future change effects.